Capturing Judgment Policies: A Field Study of Performance Appraisal - Taylor, Robert L.; Wilsted, William D. (Academy of Management Journal, 1974)
Mathematical models of judgment policy are compared in evaluating 625 performance reports during a single rating cycle. Linear and nonlinear analyses are used to describe the cues most important in determining overall ratings. In addition, performance rating policy is compared with stated policy for each of 40 raters.